STUDY ON THE AEROBIC EFFORT CAPACITY IN SOCCER PLAYERS, AT THE BEGINNING AND AT THE END OF THE COMPETITIVE PERIOD - Honceriu Cezar; Trofin Florin-Petrut (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2014)
The effort specific to the soccer game is mixed, and an important percentage is represented by the aerobic effort, under all its forms of manifestation. The purpose of our research was to assess vVO2max and tlimVO2max in soccer players, by making a comparison between two different periods: the end of the pre-competitive period (when it is considered that players have finished their training and that they have reached a plateau in their athletic shape) and the end of the competitive period. We aimed at following the evolution of these parameters, from the perspective of the specific means used in planning. Our findings indicate, except for insignificant differences, approximately equal values of VO2max and vVO2max in the two periods but also a statistically significant drop (p=0.0001) in the level of tlimVO2max. The means used during training explain both the constancy of VO2max and vVO2max, and the decrease in tlimVO2max.